آليات تلقي الصحابة – رضوان الله عليهم- للقرآن الكريم: دراسة دلالية تداولية = The mechanisms of the companions' reception of the Holy Quran: a semantic pragmatic study - Ibrahim Youssef, Mohamed Abdelrahman; Mohammad Alramadeen, Mohammad Khalil (USIM Press, 2024)
تلقّى الصحابة رضوان الله عليهم القرآن الكريم مِن فِيِّ رسول الله صلى الله عليه وسلم، عذباً نديّاً. ولم يأْلُ الصحابة جهداً في حفظ القرآن وتطبيقه في حياتهم ومعاملاتهم، ومحاولة الوقوف على مرامي الخطاب. وانطلاقاً من كَوْن الصحابة الأبرار هم الأقرب إلى رسول الله صلى الله عليه وسلم، والأعلم بمواطن النزول وأسبابه، يأتي سعي هذا البحث إلى الوقوف على الآليات التي عوَّل عليها الصحابة - رضوان الله عليهم أجمعين- عند تلقي القرآن الكريم، وذلك من منظور دلاليّ تداوليّ. وقد اُستخدِم المنهج الوصفيّ التحليليّ، وذلك بالرجوع إلى مظانّ البحث واستقرائها وتحليلها؛ للوصول إلى نتائج علمية موضوعية. وقد خلص البحث إلى عدة نتائج، منها: اتّكاء الصحابة على عدة استراتيجيات عند تلقيهم النص القرآني، ومنها: التضام، ومبدأ التشابه، والمعرفة الخلفية، ومراعاة سياق الموقف. ***** The companions (Sahaba) of the Prophet Muhammad (peace be upon him) received the Holy Quran directly from him, pure and eloquent. They spared no effort in memorizing the Quran and applying its teachings in their lives and dealings, striving to understand its deeper meanings. Given their proximity to the Prophet Muhammad (peace be upon him) and their knowledge of the circumstances surrounding the revelations, this research seeks to understand the mechanisms relied upon by the companions - may Allah be pleased with them all - when receiving the Quran, from a semantic and pragmatic perspective. A descriptive-analytical approach was employed, delving into the sources of the research, extrapolating and analyzing them to arrive at objective scientific conclusions. The research yielded several results, including the reliance of the companions on various strategies when receiving the Quranic text, such as coherence, the principle of similarity, background knowledge, and consideration of the context of the situation.